TEACHING ENGLISH AS A FOREIGN LANGUAGE TO ADULTS USING COMMUNICATIVE LANGUAGE TEACHING (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: English plays an important role in global communication and culture. Learning English for adults is necessary not only for professional development, but also for personal growth. Communicative language teaching methodology provides a communication-based approach to language learning. This article examines the main principles and methods of teaching English to adults using the communicative language teaching methodology.